'Staying strong': A constructivist grounded theory of how registered nurses deal with the impact of trauma‐related events in rural acute care practice. Issue 5 (28th August 2022) - Jahner, Sharleen; Penz, Kelly; Stewart, Norma J.; Morgan, Debra; Kulig, Judith
Abstract: Aims and objectives: This study explored how Registered Nurses (RNs) in rural practice deal with psychologically traumatic events when living and working in the same rural community over time. Background: Rural RNs who are exposed to trauma may be at high risk for psychological distress (e.g. secondary traumatic stress, vicarious trauma and post‐traumatic stress disorder), in the context of isolated practice and slower emergency response times. Design and methods: Charmaz's constructivist grounded theory methodology was chosen for this qualitative study. Purposeful sampling was used to recruit 19 RNs from six rural acute care hospitals. A total of 33 interviews were conducted with 19 face‐to‐face initial interviews, 14 follow‐up telephone interviews and 14 reflective journals. Adherence to the COREQ EQUATOR guidelines was maintained. Results: Participants were exposed to a multitude of trauma‐related events, with their main concern of being intertwined with events for life. They dealt with this by staying strong, which included relying upon others, seeking inner strength, attempting to leave the past behind and experiencing transformational change over time. Being embedded in the community left them linked with these trauma‐related events for life. Staying strong was a crucial element to their ability to cope and to face future events. Conclusions: The psychological implications of trauma‐related events when working and living in rural acute care practice settings are significant and complex. Findings highlight the need for organizational support and processes and may contribute to improved psychological services and management practices. Relevance to clinical practice: Key learnings were that rural nurses, who live and work in the same community, experience psychological changes over time from traumatic events that stay with them for life; employers fail to recognise the seriousness of this issue and trauma‐informed policies with associated resources are lacking.